EFFECT OF AGE ON POSTNATAL DEVELOPMENT OF BODY WEIGHT AND SCROTAL CIRCUMFERENCE IN ASSAM GOAT (CAPRA HIRCUS) - SARMA, KAMAL; SARMA, KAMAL; KALITA, S N; SARMA, M; DEVI, J (The Indian Journal of Animal Reproduction, 2011)
The present study was conducted on thirty Assam local goats divided into six age groups viz. group-I "(O"day), group-II (2 months), group-Ill (4 months), group-IV ( 6 months), group-V (8 months) and group-VI (10 months)consisting of five animals in each group. The mean body weight of the male kids ranged from 0.85 ± 0.03 kg at birth(group-I} to 11.26 ± 0.15 kg at the age of 10 months (group-VI). The variation in body weights were highly significant(P
Keywords: Body weight; Scrotal circumference; Postnatal development; Assam goat